Understanding Transition Matrices and Their Role in Analyzing Virus Mutation - Kumar, Nand Kishor; Yadav, Dipendra Prasad (A Bi-annual South Asian Journal of Research & Innovation, 2025)
Transition matrices are a valuable tool for understanding the mutation and evolution of viruses. They provide insights into the probabilities of genetic changes, helping researchers make informed decisions in the development of vaccines, antiviral treatments, and public health strategies. As technology and data collection methods continue to advance, transition matrices will play an increasingly significant role in our ongoing battle against viral diseases, helping us stay one step ahead of the ever-changing world of viruses.